Equilibrium stress during the response of shape memory alloys to an abrupt heat pulse. (December 2017) - Vollach, Shahaf; Caciularu, Ran; Shilo, Doron
Abstract: Previous studies of the responses of shape memory alloys (SMA) under a rapid heat pulse revealed the existence of a critical plateau stress that determines the performances of high rate SMA actuators. In this letter, we investigate the effects of temperature and initial stress on the plateau stress. Calculations based on the integration of the Clausius-Clapeyron equation while considering the inhomogeneity of the transformation temperature were in good agreement with the measured data. Our results indicate that the plateau stress represents equilibrium conditions and that actuation performances can be increased significantly by increasing the initial stress. Graphical abstract: